Modifying quantitative sensory testing to investigate tactile sensory function and behavioral reactivity in children with intellectual and developmental disabilities: establishing feasibility and testing sex, autism, and self-injury effects - Jaclyn Gunderson; Emma Worthley; Breanne Byiers; Alyssa Merbler; Andrea Huebner; Deanna Hofschulte; Jasmine Lee; Catherine Riodique; Frank Symons (Journal of Neurodevelopmental Disorders)
Abstract Background Sensory reactivity differences are common across neurodevelopmental disorders (NDDs), however very few studies specifically examine tactile or pain responses in children with NNDs, especially those with communication challenges. The current study aimed to (a) replicate the feasibility of a modified quantitative sensory test (mQST) with a sample of children with NDDs, (b) assess validity evidence based on behavioral reactivity during mQST application and the corresponding behavioral measurement coding system, and (c) explore group differences in behavioral reactivity to mQST stimuli by demographic (sex), clinical (autism status), and behavioral pathology (self-injury) variables. Methods The mQST protocol was implemented and blindly coded across 47 participants aged 2–12 years (M age = 6.7 years, SD = 2.6; 70% male) with NDDs. Feasibility was measured by completion of the mQST protocol and interobserver agreement. Validity was assessed using paired t-tests investigating differences between behavioral reactivity to active stimuli compared to a sham trial. Boxplots were used to visually explore differences in group characteristics (sex, autism status, and self-injurious behavior), with two-sample t-tests used to further characterize differences in SIB group characteristics in behavioral reactivity to mQST stimuli. Results The mQST provided codable data across 91% of stimuli applications with high IOA (84.7% [76.7–95%]). Behavioral reactivity was significantly higher for active vs. sham stimuli. Children reported to engage in self-injurious behavior showed significantly more reactivity to the second half of the repeated von Frey stimulus application compared to children without caregiver-reported self-injurious behavior (M = 6.14, SD = 3.44), t (40)= -2.247, p =.04). Conclusion The mQST is a feasible approach to investigate tactile reactivity in children with NDDs and complex communication needs. The mQST may be useful in understanding sensory variables in relation to developmental and behavioral outcomes such as self-injurious behavior.